Changes in the structure of information processes in society: opportunities and challenges in the future (Texas Journal of Philology, Culture and History, 2021)
The article analyzes the thoughts about the information web. The main signs of the information web are revealed. A number of proposals on the problems associated with the introduction of advanced information technologies are considered